Prevalence of Lumbar Spine Dysfunction in Sugar Industry Workers of Karad Taluka (Indian Journal of Public Health Research & Development, 2020)
Background: From past few years, in most of the industrialized world there has been increase in number ofindividuals having problem in musculoskeletal system. The term spinal dysfunction refers to an abnormalincrease or decrease in spinal movement (mobility). Sugar industry workers are directly involved in theproduction process that’s why some existing studies shows that the sugar industry work is characterizedby repetitive movement, heavy load movement, wrong or awkward posture, forceful activity which causescumulative trauma to the spine due to increase variability in weights.Repetitive bending movement causes backache, prolonged working hours causes feeling of fatigue, longhour movement of hand causes numbness of fingers and strenuous activities all these activities put workers atrisk for work related musculoskeletal disorders. There was hardly any literature available on the prevalenceof spinal dysfunction in sugar industry workers in rural Maharashtra. Hence this observational study is tofind out prevalence of spinal dysfunction in sugar industry workers in karad taluka.Methods: This is an observational study which included 100 subjects. Then they were screened anddistributed according to their age, gender, BMI and were asked to fill the modified oswestry low back paindisability Questionnaire. Later the subjects were assessede using modified oswestry low back pain disabilityQuestionnaire.Result: In this study 100 sugar industry workers (68 males and 32 females) were taken for study. It wasfound that 59 sugar industry workers had a lumbar spine dysfunction. The age is from 30-above 50 years ofworkers were taken in this study, which was found to be more prevalent in male(63%) than in female(50%),although this difference was not statistically significant.Conclusion: This study has provided the evidence to support the increase in lumbar spine dysfunction insugar industry workers of karad taluka.
Keywords: Lumbar spine dysfunction, sugar industry workers, modified oswestry low back pain disability Questionnaire.